Odonata Of Rice Fields In Poonch And Bagh Districts of Azad Kashmir: ?Short Communications - KHAUQ, ABDUL; SIDDIQUE, M. (Biological Sciences - PJSIR, 1995)
Rice (Oryza stiva L.), an important cereal crop of Azad Jammu and Kashmir, is grown in an area of 7,000 hectares. However, the average yield is very low (1483 Kglha) and infestation by a number of insect pests is one of the factors responsible for it.